Isolasi, Elusidasi Struktur, dan Uji Bioaktivitas Alkaloid dari Akar Kemuning (Murraya exotica L.) - Bustanussalam Bustanussalam; Titi Parwati; Partomuan Simanjuntak (JURNAL ILMU KEFARMASIAN INDONESIA, 2004)
Isolation and structure elucidation of an alkaloid, a bioactive compound from the roots of the Indonesian medicinal plant Kemuning, Murraya exotica (Rutaceae), including the brine shrimp lethality test (BSLT) have been carried out. The bioactivity test using Artemia salina, isolation and purification of the ethyl acetate extract performed by column chromatography gave yellow crystals. Based on ultraviolet, infrared, nuclear magnetic resonance (1H-&13C-NMR) and gas chromatographymass spectra the isolated bioactive compound is an indole alkaloid typical to yuehchukene.